Occupational and leisure-time physical activity differentially predict 6-year incidence of stroke and transient ischemic attack in women - Hall, Clinton; Heck, Julia E.; Sandler, Dale P.; Ritz, Beate; Chen, Honglei; Krause, Niklas (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVES ': 'Recent meta-analyses suggest a physical activity health paradox: high levels of occupational physical activity (OPA) increase cardiovascular disease (CVD) risk, while leisure-time physical activity (LTPA) decreases risk. However, studies of women and cerebrovascular disease are limited. This report examines physical activity effects on stroke and transient ischemic attack (TIA) among working women in the United States. ' ' METHODS ': 'OPA history, health status, and lifestyle were assessed by baseline interviews of 31 270 employed Sister Study participants aged 35–74 years. OPA was assessed at six intensity levels (lowest: “mostly sitting”); the highest three were combined as “high intensity work.” Independent OPA and LTPA effects on 6-year cerebrovascular disease incidence were estimated in adjusted Cox proportional hazard models. ' ' RESULTS ': 'Stroke (N=441) and TIA (N=274) risk increased with more standing and higher intensity work at current and longest held job. Compared with mostly sitting, high intensity work at the current job increased TIA risk by 57% [hazard ratio (HR) 1.57, 95% confidence interval (CI) 1.04–2.38]. High intensity OPA at the longest held job increased risk for stroke by 44% (HR 1.44; 95% CI 1.08–1.93). Among women with CVD, sitting and standing equally, especially at the current job, increased risks up to two-fold (TIA HR 1.98, 95% CI 1.10–3.55) compared with mostly sitting at work. LTPA showed inverse associations. ' ' CONCLUSIONS ': 'Higher intensity levels of OPA increased stroke and TIA risks, while LTPA decreased risks; results corroborate the physical activity health paradox for women and cerebrovascular disease. More standing at work increased cerebrovascular disease risks, especially for women with CVD.
Keywords: cerebrovascular disease; cohort; epidemiology; incidence; ischemic heart disease; leisure-time physical activity; occupational physical activity; physical activity; physical activity health paradox; prospective; stroke; transient ischemic attack; women; work posture